Undesired nexus poor health status of child under-five: A case study of Pakistan - Urva Zainab; Mohsin Abbas; Amena Urooj; Mahwish Rabia; Huaping Sun; Muhammad Ahmed Shehzad (PLoS ONE, 2025)
Childhood morbidity and mortality are key indicators of human development, particularly reflecting poor health conditions in children. In Pakistan, child mortality remains a serious problem despite efforts to reduce it. One factor that may be associated with child mortality is an undesired pregnancy, whether unwanted (the parents did not want more children) or mistimed (the pregnancy occurred earlier than desired). Unwanted pregnancies and births are psychological factors that negatively impact children’s nutritional health. The main objective of the study is to measure the impact of mothers’ aspired status on child mortality and morbidity in Pakistan. We limited our analysis to children under 5 before the survey and used Pakistan demographic health survey conducted in 2017-2018, a national representative cross-sectional survey. We were able to predict the unwanted state (excess in boys, girls, both, and parity) by subtracting the ideal number of children from total live births. Morbidity (fever, diarrhea, cough, acute respiration infection, and Short rapid breathing), nutritional status, and mortality were also evaluated. We perform machine learning techniques such as random forest (RF) and neural network (NN) in the analysis of the data. The findings revealed that the overall percentage of the undesired child was 8%, 4%, 15%, and 27% for boys, girls, parity, and dual excess, respectively. Finally, we perform multivariate analysis following the principal component analysis (PCA) to study the relationship between variables. All the variables were associated with the unwanted child. Child morbidity, fever, and cough were higher among the undesired children. We found evidence that undesired children have acute respiration infection and that an unwanted child has a significant impact on childhood diseases. The ratio of child mortality was lower for boys but higher for girls.